Theory and Practice of Natural Computing Third International Conference, TPNC 2014, Granada, Spain, December 9-11, 2014. Proceedings - Dediu, Adrian-Horia; Lozano, Manuel; Martín-Vide, Carlos (Theoretical Computer Science and General Issues, 2014)
This book constitutes the refereed proceedings of the Third International Conference, TPNC 2014, held in Granada, Spain, in December 2014. The 22 revised full papers presented in this book were carefully reviewed and selected from 47 submissions. The papers are organized in topical sections on nature-inspired models of computation; synthesizing nature by means of computation; nature-inspired materials; and information processing in nature.